Synthesis, Characterization and Biological Activities of 5,5,-(ethane-1,2-diyl)bis(4-(4-nitrobenzylideneamino)-4H-1,2,4-triazole-3-thio) and its Complexes with Cu(II), Cd(II), Hg(II) and Ag(I) ions - Nada A. Rasheed (Journal of Global Pharma Technology, 2018)
A series of coordination compounds of Cu(II), Cd(II) , Hg(II)  and Ag(I) ions with 5,5, -(ethane-1,2-diyl)bis(4-(4-nitrobenzylideneamino)-4H-1,2,4-triazole-3-thio) , as a ligand has been successfully prepared in alcoholic medium. The synthesized complexes were characterized quantitatively and qualitatively by using: elemental analysis CHNS, FT-IR spectroscopy, UV-visible spectroscopy, 1H and 13CNMR, atomic absorption measurements, magnetic susceptibility, thermal analysis)TG and DTG) and conductivity measurements . This ligand coordinates as a bidentate that to the metal ions through sulphur and nitrogen of (azomethine group) atoms. According to the spectral data, Cu(II)- complex has coordination of 6 with octahedral geometry while the Cd(II)-complex and Hg(II) have coordination of 4 with exhibited tetrahedral ,and the Ag(I)-complex has coordination of 3 with exhibited trigonal planer ,  The Schiff base and its metal complexes have been screened for antimicrobial activity against four  bacteria, namely :(Staphylococcus aureus, , Streptococcus sp. , Klebsilla Pneumonia  Escherichia coli )and the  fungi, namely ( Aspergillus flavus ) .Keywords: Triazole complexes; Schiff base-triazole; Biological activity.